Melatonin protects against pressure ulcer-induced oxidative injury of the skin and remote organs in rats - (:unkn) unknown (WILEY, 2006)
Pressure ulcers (PU) cause morphological and functional alterations in the skin and visceral organs; the damage is believed to be due to ischemia/reperfusion (I/R) injury. In this study, we examined the role of oxidative damage in PU and the beneficial effect of treatment with the antioxidant melatonin. PU were induced by applying magnets over steel plates that were implanted under the skin of rats; this compressed the skin and caused ischemia. Within a 12-hr period, rats were subjected to five cycles of I/R (2 and 0.5 hr respectively), followed by an additional 12 hr of ischemia (to simulate the period at sleep at night). This protocol was repeated for 3 days. In treatment groups, twice a day during reperfusion periods, melatonin (5 mg per rat) was either applied locally as an ointment on skin, or administered i.p. (10 mg/kg). At the end of the experimental period, blood and tissue (skin, liver, kidney, lung, stomach, and ileum) samples were taken for determination of biochemical parameters and for histological evaluation. Local treatment with melatonin inhibited the increase in malondialdehyde levels; an index of lipid peroxidation, myeloperoxidase activity; an indicator of tissue neutrophil infiltration, and the decrease in glutathione; a key antioxidant, in the skin induced by PU, but was less efficient in preventing the damage in visceral organs. However, systemic treatment prevented the damage in the visceral organs. Significant increases in creatinine, blood urea nitrogen, alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase and collagen levels in animals with PU were prevented by melatonin treatment. The light microscopic examination exhibited significant degenerative changes in dermis and epidermis in the PU rats. Tissue injury was decreased especially in the locally treated group. Findings of the present study suggest that local and/or systemic melatonin treatment may prove beneficial in the treatment of PU.
Keywords: antioxidant; decubitus ulcer; glutathione; lipid peroxidation; melatonin; myeloperoxidase; ISCHEMIA-REPERFUSION INJURY; MYELOPEROXIDASE ACTIVITY; FREE-RADICALS; TISSUE; OXYGEN; MECHANISMS; OXIDANTS